Productivity reimagined shattering performance myths to achieve sustainable growth - Stoller, Jacob (Ascent Audio, 2024)
Written by Shingo Prize winner Jacob Stoller, Productivity Reimagined shows how most companies are constrained by deeply engrained myths that prevent employees from reaching their full productive potential, causing frustration, poor decisions, and disappointing results. Evidence is drawn from Toyota and dozens of other companies that have countered these myths to build strong collaborative cultures and achieve sustainable growth. Arguments are reinforced by the latest science on human behavior and systems theory and supported by more than sixty interviews from prominent CEOs, consultants, academics, executive directors, and EVPs in the context of today's pressing global issues, including labor shortage, income inequality, job-related stress, supply chain instability, and climate change. As companies face the new realities of the global economy, Productivity Reimagined is an essential resource for forward-thinking executives, managers, and business leaders looking to solve the productivity puzzle and empower their workforces to perform at their best.
Online resource; title from title details screen (O'Reilly, viewed October 29, 2024)
Keywords: Industrial productivity; Labor productivity; Production (Economic theory); Sustainable development; Productivité; Production; Développement durable; sustainable development; Audiobooks; Livres audio